ANALISIS KESULITAN MAHASISWA CALON GURU FISIKA DALAM MEMAHAMI KONSEP GERAK PARABOLA - Saeful Karim; Duden Saepuzaman (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2016)
This research is motivated by the achievement of student learning outcomes Physics 1 were not as expected. Further analysis of the results of student answers, found one of the concepts are still low achievement of learning outcomes is the projectile motion. Projectile Motion is part of the topic of the two-dimensional motion. The purpose of this study is to investigate and uncover the difficulties experienced by students on the concept of a projectile motion in order to plan appropriate learning program. The method used is descriptive analysis with a sample of 42 students who take the Basic Physics Course I on LPTK in West Java. Collecting data form of essai test. Based on the test results, it is known that students have difficulty following. First, drawing the vector component in the direction x (horizontal) and y (vertical). Second, distinguish the velocity vector, the vector component of velocity, the velocity vector component in the x and y directions. Third, focus on memorizing formulas bullet time taken for half a parabolic trajectory, maximum of height, maximum of distance. Fourth, always assumed final velocity moving object parabola when it hits the ground is always zero. Fifth, the velocity to zero at the top (when only the speed in the vertical direction is zero). Sixth, the acceleration is owned by the object in the x and y directions. Seventh, found some students use the law of sines cosines triangle on the determination of the distance / high and reverse (ideally the determination of the distance / high based on the velocity information). Keywords: difficulties leraning , preservice physics teacher , projectile motion.